Lipid-Lowering Efficacy of the Capsaicin in Patients With Metabolic Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Jiang, Zhonghui; Qu, Hua; Lin, Gongyu; Shi, Dazhuo; Chen, Keji; Gao, Zhuye (Frontiers in Nutrition, 2022)
Background: Patients with metabolic syndrome (MetS) have increased cardiovascular risk. Capsaicin (CAP) has been shown to reduce lipids, but efficacy for patients with MetS is unknown. Methods: A systematic review was performed according to PRISMA guidelines, to compare the effects of CAP against a placebo. Differences in the weight mean difference (WMD) with 95% confidence intervals (95% CI) were then pooled using a random effects model. Results: Seven randomized controlled trials including 461 patients were identified in the overall analysis. CAP significantly decreased total cholesterol (TC) (WMD = -0.48, 95% CI: -0.63 to -0.34, I2 = 0.00%) and low-density lipoprotein cholesterol (LDL-C) (WMD = -0.23, 95% CI: -0.45 to -0.02, I2 = 68.27%) among patients with MetS. No significant effects of CAP were found on triglyceride (TG) or high-density lipoprotein cholesterol (HDL-C) (WMD = -0.40, 95% CI: -1.50 to 0.71, I2 = 98.32%; WMD = -0.08, 95% CI: -0.21 to 0.04, I2 = 86.06%). Subgroup analyses indicated that sex and intervention period were sources of heterogeneity. The results revealed that CAP decreased TG levels in women (WMD = -0.59, 95% CI: -1.07 to -0.10) and intervention period less than 12 weeks (WMD = -0.65; 95% CI: -1.10 to -0.20). And there was no potential publication bias according to funnel plot, Begg’ test and Egger regression test. Conclusions: CAP supplementation is a promising approach to decreasing TC and LCL-C levels in patients with MetS. However, short-term (< 12 weeks) use of CAP in women may also reduce TG levels.